The Current Insecticide Resistance in Main Malaria Vector Anopheles arabiensis in Yemen. (30th March 2020) - Al-Koleeby, Zalalham; El Aboudi, Ahmed; Assada, Mithaq; Al-Hadi, Mohamed; Abdalr Ahman, Mohammed; Awash, Abdullah; Ahmed, Abdul Samad; Mohamedi, Hani; Al Jarbany, Jamil; Faraj, Chafika
Abstract : Control of malaria vectors in Yemen relies on both indoor residual spraying using carbamate (bendiocarb) and long-lasting pyrethroids-treated nets. This paper reports the results of studies conducted to monitor the insecticide resistance of the main malaria vector, Anopheles arabiensis, to the insecticides currently used in the vector control in four different locations. Susceptibility tests were performed following the WHO test procedures. Two pyrethroids (lambda-cyhalothrin 0.05% and deltamethrin 0.05%) and one carbamate (bendiocarb 0.1%) were tested at diagnostic doses (DD). The five-fold DD of lambda-cyhalothrin and deltamethrin (0.25%) were also used to yield information on the intensity of resistance. Besides, tests with synergists were performed to assess the involvement of detoxifying enzyme in the phenotypic resistance of the populations of An. arabiensis to pyrethroids. The results of the performed susceptibility bioassay showed that the vector is susceptible to bendiocarb and resistant to lambda-cyhalothrin and deltamethrin in the four studied areas. The pyrethroids resistance is solely metabolic. This information could help policy-makers to plan insecticide resistance management. Bendiocarb is still an effective insecticide in the form of IRS. Concerning LLINS, it would be interesting to assess their effectiveness, combining a pyrethroid with PBO for the control of the pyrethroid-resistant malaria vector.